2004
DOI: 10.1593/neo.03460
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Targeted Hyaluronan Nanoliposomes Increase the Antitumor Activity of Liposomal Doxorubicin in Syngeneic and Human Xenograft Mouse Tumor Models

Abstract: Naturally occurring high-Mr hyaluronan, bound to the surface of nanoliposomes (denoted targeted hyaluronan liposomes, or tHA-LIP), is a candidate for active targeting to tumors, many of which overexpress the hyaluronan receptors CD44 and RHAMM. The surface-bound hyaluronan also provides a hydrophilic coat that, similar to polyethylene glycol, may promote long-term circulation. We recently reported the successful targeting of mitomycin C, mediated by tHA-LIP, in tumor-bearing syngeneic mice. Hypothesizing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 33 publications
(29 reference statements)
6
161
0
Order By: Relevance
“…This type of active targeting has been used previously to increase cellular uptake of doxorubicin-loaded liposomes ($20-fold; ref. 40). However, this work is different from most prior studies, in that the other studies used high molecular weight hyaluronic acid (>75 kDa) as the drug carrier (28,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 88%
“…This type of active targeting has been used previously to increase cellular uptake of doxorubicin-loaded liposomes ($20-fold; ref. 40). However, this work is different from most prior studies, in that the other studies used high molecular weight hyaluronic acid (>75 kDa) as the drug carrier (28,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 88%
“…56,57) Huang and coworkers demonstrated that a PEGylated liposome-polycation-dNA nanoparticle (LPD) modified with anisamide on top of PEG efficiently delivered siRNA to lung carcinomas with high expression levels of sigma receptors, which resulted in luciferase gene silencing in metastatic tumors compared with nontargeted PEGylated LPd. 58,59) Antibodies have been widely investigated as ligands for the tumor targeting of liposomes due to their high specificity and affinity for target molecules.…”
Section: -28)mentioning
confidence: 99%
“…Pharmacokinetic properties, such as circulation time and biodistribution, are influenced by incorporating the targeting and cellspecific uptake properties of HA onto large carriers. Cargos delivered to CD44 over-expressing cells include anti-cancer drugs: epirubicin, 14 doxorubicin, 37,38,41,69,70,71 paclitaxel, 28,29,62,63 and mitomycin c, 14,70 as well as agents such as siRNA, 72 iron oxide magnetic particles, 73 and DNA. 74 These studies are summarized in Tables 3 and 4. Several different methods have been used to improve the distribution of doxorubicin, which has significant cardiotoxicity as a free drug.…”
Section: C Hyaluronan In a Targeted Nanocarrier Systemmentioning
confidence: 99%
“…Liposomes (nanosized phospholipid vesicles) bearing oligosaccharide HA conjugated to a phosphatidylethanolamine lipid have been used as a targeted drug carrier for doxorubicin. 37,38,41,69,70 Two different approaches to attach HA to liposomes were developed. 41,75 In the earliest report, HMW-HA was coupled via the glucuronic carboxylate to phosphatidylethanolamine in pre-formed liposomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation